(Il) disfarsi della città: là dove c’era una fabbrica ora c’è l’erba infestante - Vinai, Manuela (Antropologia Pubblica, 2025)
Biella, ritratto di una città fabbrica was a 2019 project that, through a “wall exhibition”, provided a vivid visual narrative of the city’s industrial past, using photographs and documents from Biella’s archives. The focus, as indicated by the title, was on the city’s industrial history. In early 2022, the Est-Urbano project was launched, in which I was directly involved. Its goal was to foster collective reflection on a “complex” part of the city: “a few square kilometers of regenerated industrial areas housing renowned foundations, the former Ospedale degli Infermi, the abandoned Lanifici Rivetti factories, a notable natural balcony, an imagined “city forest,” a cultivated area for organic farming supported by sustainable agricultural networks, active factories like the Lanifici Cerruti complex, and two neighborhoods with schools and activities, plus the main train station”. This contribution presents an ethnography of the participatory process shared with a group of citizens during ten months of collaborative work that marked a journey of responsibility and dialogue about the vacant Lanifici Rivetti and Pettinature Rivetti factories. The analysis reveals the roles of various social actors and explores the interaction with the non-human, highlighted by the juxtaposition of factories with the “natural balcony” and “city forest.” Particularly, the study focuses on the black locust (Robinia) offering insights into “weedy emergence” (Tsing 2017). The analysis thus centers on abandoned urban areas and their repurposing, acknowledging that, as anthropologist Morisset notes, it is “impossible, en effet, d’espérer requalifier la ville sans faire de même de sa société” (2017, p. 49).